Mastoid surgery: a high-risk aerosol generating surgical procedure in COVID-19 pandemic - Swain, Santosh Kumar; Agrawala, Rohit (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Corona virus disease 2019 (COVID-19) is highly contagious disease occurred by the severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) which spreads human to human through respiratory secretions. It was declared as public health emergency all over the world. There is lack of data in relation to the otologic or mastoid surgery during COVID-19 pandemic. Aerosolization of the novel corona virus SARS-CoV-2 is associated with middle ear and mastoid surgery. So, the safety precautions are important parts in this present pandemic time for preventing transmission of the infections to the surgeon and team members of the surgery. Preoperative screening for COVID-19 is must for safety of the surgeon and team members. The mastoid surgery on the positive, suspected or unknown status for COVID-19 patients need protection with adequate Personal protection equipment (PPE) such as disposable cap, N95 respirator and sealed eye protection or Powered air-purifying respirator (PAPR), disposable gown and gloves. In the mastoid surgery, there is scarcity of the medical literature related to the transmission of the novel corona virus SARS-CoV-2and its prevention during present COVID-19 pandemic. So, the aim of this review article is to increase awareness among the otolaryngologists for preventing the viral exposure during the mastoid surgery.